ROLE OF FNAC IN BONE LESIONS, A CYTOLOGICAL AND HISTOLOGICAL CORRELATION IN A TERTIARY CARE CENTER IN CENTRAL INDIA - SINGH, PUJA; JOHER, MUNIRA; MERAVI, JYOTI; TRIPATHI, SONALI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: FNAC plays a pivotal role in any lesion for the ease of diagnosing and treatment of an ailment. The role of FNAC in bone lesions has not been studied in great vastness but it can definitely ease the time taken for diagnosing on histopathology. The aim of the study was to study the sensitivity, specificity, positive predictive value, and negative predictive value of FNAC in bone lesions, comparison of cytological findings to histopathological findings and to identify the accuracy of FNAC in bone lesions. Methods: The study was retrospective and observational study. All the FNAC samples were studied and correlated with the histopathology findings where available. Results: A total of 92 cases were studied. The accuracy of the study stands at 81.3% along with the sensitivity of 87.5% and specificity of 75% with a positive predictive value of 77.8%. Non-neoplastic lesions were 18, followed by primary benign bone tumors 29, Primary malignant bone tumors 28, secondary tumors of bone 6, and unsatisfactory smears 11 cases were identified. Conclusion: FNAC plays a very crucial role in diagnosing and early intervention and treating any ailment. Bone FNAC also is beneficial for identifying the treatment modality. It should be used on regular basis for bone lesions.